The use of translation as a teaching method in second language teaching: a case study with second language learners of isiXhosa at the University of Cape Town - Ngwendu, Amandla (African Languages and Literatures, 2017)
This research topic came about during my honours research project. The honours project studied strategies that are used by second language learners in acquiring vocabulary. One of the strategies that were used was direct translation. Upon further research into the subject, it was we discovered that no work has been done on the use of translation as a teaching method in isiXhosa. This study attempts to bridge the information gap in the area of second language learning and teaching in African languages. The current study followed two classes at University of Cape Town where isiXhosa literature is taught as a second language. Given that the students do not speak any isiXhosa at entry level, they rely heavily on their first language for making sense of the second language. In the case of literature, where terminology is not carefully selected to accommodate second language learners, students rely heavily on translation. This study therefore investigates the role and process of translation as a teaching method. The lack of research in this area made it very difficult to follow a particular theoretical framework, therefore the study followed a mixture of qualitative and quantitative approaches. Students were given activities that would require translation in order for the task to be completed. This forms part of their normal learning process. These activities were analysed. The second part consisted of a questionnaire that surveyed the student's views regarding the use of translation. Findings based on the qualitative data analysis revealed heavy relianace on translation as a learning strategy. Students also indicated that prior knowledge of vocabulary as well as an understanding of morphology were both very beneficial.